The power of gold : - Bernstein, Peter L. (John Wiley & Sons, 2000)
"[T]he quest for gold" has been "gluttonous," says Bernstein, tracing the metal's impact on human myth and history: gold has inspired art, battles, conquests and discoveries, including Columbus's trip to the New World, where he hoped to secure enough gold to buy back the Holy Sepulcher from the Muslims. Bernstein makes clear the metal's virtues: it's so malleable that one ounce can be stretched into a 50-foot wire or pounded into 100 square feet, and it lasts forever (4,500-year-old Egyptian dental work, he notes, is good enough for today's mouths). Bernstein's gift for storytellingAwith just the right touch of acerbic wit (on the myth of Jason and the Golden Fleece, he summarizes, "The story does not have a happy ending, because Jason was a compulsive social climber")Aand his presentation of the paradox of how and why such a soft and simple metal has been afforded such value help make this work a winning account of human obsession, comprehensive, entertaining and enlightening. A knowledge of economics might help during the last third of the book, when Bernstein moves from ancient times to modern day and describes the economic chaos that followed WWI. By then gold was no longer the domain of legend; it had become a commodity, the standard against which powerful nations measure their wealth. But Bernstein, author of the bestselling Against the Gods: The Remarkable Story of Risk, livens up his intricate economic discussion with tales such as the one about the Harvard Business School professor who got into trouble with his dean for withdrawing his gold from the Harvard Trust Company during a gold standard-related panic in 1933. As the title promises, Bernstein does deliver a page-turning history of the not-so-heavy metal and its influence on people through the ages.